(untitled) (Proceedings OPTIMAL, 2025)
Background: Malaria remains a significant public health problem in Indonesia, particularly in Papua. Lavender essential oil (Lavandula angustifolia) is a natural alternative repellent, but its high volatility and irritant potential limit direct application. To overcome these limitations, a stable and effective emulgel formulation was developed. Carbopol 940 was chosen as the gelling agent due to its high viscosity and compatibility, with concentration expected to strongly influence physical properties. Objective: This study aimed to evaluate the effect of Carbopol 940 concentration on the physical quality of lavender essential oil emulgel formulations. Methods: An experimental design was conducted with three formulas: F1 (1% Carbopol 940), F2 (1.5%), and F3 (2%). Data were analyzed using one-way ANOVA. Results: All formulations exhibited white color, characteristic lavender aroma, and uniform emulgel consistency. Homogeneity was observed across all samples. The pH was 5.0 for F1 and F2, and 6.0 for F3. Spreadability decreased as Carbopol concentration increased (5.84 cm for F1, 4.93 cm for F2, 3.97 cm for F3). Adhesion showed the opposite trend (5.68 s, 10.49 s, and 13.27 s, respectively). Viscosity also increased with higher concentrations (4,920 cP, 13,060 cP, and 24,380 cP). All formulas remained stable with no phase separation during thermodynamic stability testing. Conclusion: Variations in Carbopol 940 concentration significantly influenced emulgel physical properties